Acute pulmonary embolism following corticosteroid administration in acute severe ulcerative colitis with gastrointestinal bleeding: A case report - Liu, Xuhan; Peng, Xia; Rong, Chunyan; Zhang, Weihua (Frontiers in Cardiovascular Medicine, 2022)
Background Ulcerative colitis often leads to gastrointestinal bleeding and venous thromboembolism (VTE). At present, there is no clear conclusion about anticoagulant therapy for these patients. Treatment for ulcerative colitis usually includes 5-aminosalicylic acid, corticosteroid, and biologics. Acute ulcerative colitis, usually caused by infection, is usually severe and can be life-threatening. Case presentation We report the development of VTE in a patient with severe acute ulcerative colitis who experienced gastrointestinal bleeding following hormonal therapy. The patient's indicators suggested that his blood was hypercoagulable and that his prognosis was poor. Conclusion Patients with ulcerative colitis are prone to form VTE. The use of corticosteroids during treatment increases the risk of thrombus. Anticoagulation strategy for patients with ulcerative colitis after gastrointestinal bleeding is a problem that needs to be discussed.